PENERAPAN MEDIA PERMAINAN ONLINE “BAAMBOOZLE” UNTUK MELATIH POSSESIVPRONOMEN IM AKKUSATIV BAGI SISWA KELAS XI BAHASA 2 SMA NEGERI 7 MALANG - Gaye, Karina Salsabilla Kartika Putri (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
The research sets out to describe how the application of Baamboozle online game media was used to train Possesivpronomen im Akkusativ grammar for students in XI Language class 2 at SMAN 7 Malang and to describe their responses. This research used a descriptive qualitative method. The data of this research are informative verbal data related to the application of the online game media Baamboozle. The data was collected using observation and some questionnaires. In this research, the data was analyzed interactively using the Miles and Huberman model through three steps, such as data reduction, data display, and conclusion-drawing presented in descriptive paragraphs. The results showed that the lesson plan was properly followed when appliying the Baamboozle online game media. Through the application of this game media, the Possesivpronomen im Akkusativ grammatical material can be easily understood and applied by students. Students response to the presentation of the Possesivpronomen im Akkusativ material using the online game Baamboozle were very positive. Students can easily understand and apply the grammatical material. It is suggested that German language teachers use this Baamboozle online game media based on the report’s result and next researchers should be able to investigate moreover about this Baamboozle online game media on other German grammatical materials in an integrative way with German language skills such as reading (Lesefertigkeit) and speaking (Sprechfertigkeit) skills.